GAMIFICATION OF MOBILE-BASED JAPANESE LANGUAGE SHADOWING - Christian Kurniawan, Hans
Shadowing, a language learning method especially well-known in Japanese language, is a technique of hearing audio how to pronounce a word or sentence correctly, and then repeat it as close as possible. This technique is effective for learning new vocabularies as well as improving speaking skill which is often not focused on Japanese language school because it doesn’t included in JLPT exam material. However, practicing shadowing independently also tends to be boring, lack of motivation to finish learning materials, less challenging, no peer partner, and no teacher to assess whether the pronounciation is correct or not. On the other hand, gamification as a technique for applying game elements in non-game context applications, can be applied to make a fun, interesting, and challenging learning environment that continues to motivate student to achieve better result. There are various gamification elements that can be applied such as progression, virtual currency, storyline, rewards, badges, leaderboard, etc., which one of each has its own influence on student’s motivation. One of the essential element is direct-feedback to determine whether the answers given by the students are already correct or not, by calculating similarity between student’s speech and reference speech. Feature extraction method using Mel-Frequency Cepstral Coefficients (MFCC) and Dynamic Time Warping (DTW) are used to compare the similarity between two sounds with different speed. In this study, “Shadowingu”, a gamified Japanese language learning application based on mobile platform, is developed. The evaluation results showed that 92% of respondents preferred “Shadowingu” rather than the conventional shadowing method, with Effect Size range from Medium to Very Large for each ARCS motivation component (Attention, Relevance, Confidence, Satisfaction). There is a combination of 15 gamification elements applied on Shadowingu app and all of them have had a positive effect on students. In addition, “Shadowingu” app also has a “Good” application quality according to SUS scale, so it is feasible to be used as a learning medium.